Sebaran dan Zonasi Krustasea Mangrove di Delta Mahakam, Kalimantan Timur - Rianta Pratiwi (Fakultas Biologi | Universitas Jenderal Soedirman, 2006)
A study on the distribution and zonation of mangrove crustacean in Mahakam Delta, East Kalimantan was conducted in July 2004. The three research locations were selected i.e. Muara Ilu, Muara Kaeli, Muara Bayor and Muara Beji. Crustaceans were collected by applying quandran methods (1 x 1 m) in transect lines. The diversity index (H’) of crustacean in Delta Mahakam: 1.382 - 2.028 and the Eveness index (E) : 0.5877 - 0.7101. The highest diversity index was recorded from muara Kaeli and the highest Evenes index was in Muara Ilu.